Influence of Parental Alcohol Consumption among Schooling Adolescent Students - Sharma, Bhagawoti; Devkota, Bhimsen (KMC Journal, 2025)
Alcohol consumption among school students is a growing concern worldwide. Parental influence plays a crucial role in shaping the alcohol consumption behavior of adolescent students. This study aimed to explore the influence of parental alcohol consumption, monitoring, and communication among adolescents’ alcohol consumption. This study followed a descriptive research design and employed a cross-sectional survey to collect quantitative data. The study population for this research included school students studying at the secondary level in the public secondary schools of Banke District. The researcher selected 422 students by using multistage sampling. The self-administered questionnaire was used as the tool for quantitative data collection. The collected quantitative data were entered into the computer and analyzed subsequently using SPSS version 27. Descriptive statistics were used to analyze data, e.g., frequency and percentage analysis, and important study findings were presented. Binary logistic regression was used to analyze the effects of parents’ monitoring, parent-student communication, parents’ alcohol consumption, and alcohol consumption among school students. The results of the study showed that parental alcohol consumption (both mother and father) is significantly associated with lower adolescent alcohol consumption. Likewise, parental monitoring decreases adolescent alcohol consumption. Furthermore, parental communication with their children about alcohol is not significantly related to adolescent alcohol consumption. The findings suggest the necessity of anti-alcohol educational interventions for controlling alcohol consumption among school students as well as minimizing parental influence on adolescent alcohol consumption.